Implementasi Indonesia Portnet dalam Memberikan Pelayanan Kepada Pengguna Jasa di Lingkungan Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas III Sampit - Waskito, Rizky Davela Bagas; Aripin, Sofjan; Siahaan, Asima Yanty (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the implementation of the Indonesia PortNet (Inaportnet) system in improving the quality of port services at the Office of Harbormaster and Port Authority (KSOP) Class III Sampit. The application of this system is part of the public service digitalization policy initiated by the Indonesian Ministry of Transportation. Using a qualitative approach through interviews, observations, and document analysis, the study found that Inaportnet has had a positive impact on service efficiency and transparency. However, its implementation has not been fully optimized. The main challenges include limited user understanding of the digital system, inadequate human resources, and complex bureaucratic structures. Based on George C. Edward III’s policy implementation theory, communication, resources, disposition, and bureaucratic structure are critical factors influencing success. Therefore, enhanced outreach, capacity building, and procedural simplification are needed to improve the effectiveness of Inaportnet.